Large pancreatic mass with chylous ascites. Issue 1 (2nd January 2020) - Badrinath, Madhuri; Tambe, Ajay; Mandru, Rachana; Saleem, Sheikh; Heisig, David
Abstract: Primary pancreatic lymphoma (PPL) is a rare entity, most likely to be clinically misdiagnosed as pancreatic adenocarcinoma. The cure rate of PPL is higher than that of adenocarcinoma. We present a case of PPL that presented as a pancreatic mass with chylous ascites and describe the incidence, clinical features, diagnostic approach, and most commonly used treatment regimens for PPL.